Identifying Gender Bias in the Short Film "Padanan" : Mengidentifikasi Bias Gender dalam Film Pendek “Padanan" - Raihana, Yasmin; Fikri, M. Andi (House of Wisdom: Journal on Library and Information Sciences, 2025)
General background : Gender bias remains a persistent social issue with widespread, often implicit, manifestations that negatively impact social and professional dynamics. Specific background : The short film "Padanan" was produced to raise awareness about and prevent these subtle gender bias behaviors by portraying them within a narrative context. Knowledge gap : While the film offers a compelling artistic representation, a formal, qualitative analysis to systematically categorize and explain the specific types of bias depicted has been lacking. Aims : This study, therefore, aims to identify, explain, and analyze the various gender bias behaviors portrayed in "Padanan" through a qualitative methodology focused on documentary analysis. Results : The findings reveal five distinct forms of gender bias: marginalization, sexual violence, stereotypes, double burden, and subordination. Novelty : This research provides a unique, theory-supported framework for categorizing implicit gender bias as it is presented in modern media. Implications : The results offer significant insights for raising public awareness and developing targeted interventions to address and prevent these harmful behaviors. Highlights : The short film "Padanan" was created to address and prevent implicit gender bias behaviors. The research identified five types of gender bias: marginalization, sexual violence, stereotypes, double burden, and subordination. The film's production used a qualitative methodology, analyzing the short film "Padanan" to describe social phenomena related to gender. Keywords : Gender Bias, Women Empowerment, Padanan Film, Qualitative, Stereotypes